Diagnosing the Reality of the Jordanian Experience in Guaranteeing Deposits with Islamic Banks - khelif, Abd rahmen; medaouakh, Madjda (Finance and Business Economies Review, 2022)
This study aims to analyze the availability of a system to guarantee bank deposits in Islamic banks that is compatible with the provisions of Islamic Sharia, as it is a modern mechanism that aims to protect deposits in Islamic banks from losses and hedge against banking risks, as well as to enhance financial stability. Islamic banks have a subject for study and discussion in terms of addressing the nature of this fund, its mechanism of action, and its suitability to the nature of Islamic banking work. Through this study: The necessity of establishing special funds to guarantee the deposits of Islamic banks on the basis of takaful in accordance with the provisions of Islamic Sharia and working under the supervision and control of the Central Bank to avoid the occurrence of cases. From default and bankruptcy.